Encapsulation for organic photovoltaics - Chatzipapa, Antri (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2016)
In the beginning of this project work, a study was made on normal structures of Organic Photovoltaics (OPV) cells (bulk heterojunction). The next step was to examine the lifetime of Organic Photovoltaics and to find ways to increase it. The study became more specific, shifting the examination to Indoor Accelerated Lifetime. Following all these steps it was decided that in order to extend the lifetime in organic photovoltaics an encapsulation was necessary to help the process. So, it was decided to apply an encapsulation on an OPV cell with a bulk heterojunction structure, with the use of zeo, ossila and dymax3089. The final goal was to achieve an extended lifetime for Organic Photoltaics, i.e. live further without the yield of PCE drops below 80%. Due to several malfunctions, during the experimental process, three types of glues were encapsulated, zeo, ossila and dymach.. The comparisons were made among ossila - dymax 3089 and ossila-zeo. The results showed that ossila is able to extend the lifetime of organic photovoltaics 21 times more than dymax 3089 is, thus, undoubtedly ossila is much better than the dymax 3089. Comparing ossila with zeo, zeo increases the lifetime of organic photovoltaic six times more than ossila does. So, according to the measurements of the specific study, it can be resulted that if an organic photovoltaic is encapsulated with zeo eraser then its lifetime will be extended more than with an encapsulation of ossila and dymax 3089. However, it still needs further research, for instance, to use more kinds of glues to have more accurate results.
Keywords: Organic Photovoltaics (OPV); Indoor Accelerated Lifetime